Measurement of In-Plane Strain with Shearography and Electronic Speckle Pattern Interferometry for Composite Materials - Cordero-Carrasco, R (Institute of Electrical and Electronics Engineers Inc., 2014)
Experimental results obtained by applying both technique, Electronic Speckle Pattern Interferometry (ESPI) and Electronic Speckle Pattern Shearing Interferometry (ESPSI) were compared in the study of composite materials. We found that the difference between the strain fields obtained by ESPSI and ESPI was roughly a constant. This result was expected since, although ESPI in turn allows computing absolute strain values, the strains measured by ESPSI are relative to a reference that must be measured by an additional method. © 2014 IEEE.
Keywords: Electronic Speckle Pattern Interferometry; Shearography